The Effectiveness of Argumentative Speaking Skills Learning Using Think-Pair-Square and Think-Pair-Share Models Assisted by Podcast Based on Students’ Personality Types - Muhammad Jahfal Hanan; Rahayu Pristiwati; Muhammad Jahfal Hanan (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study examined the effectiveness of learning argumentative text speaking skills using the Think-Pair-Square and Think-Pair-Share models assisted by podcast media while considering the pe of twelfth-grade high school students. This research employed a quasi-experimental method. The subjects were twelfth-grade students at a senior high school, with class XII-4 as the experimental class and class XII-5 as the control class selected through purposive sampling. The independent variables were the Think-Pair-Square and Think-Pair-Share models assisted by podcast media, while the dependent variable was argumentative text speaking skills. Students’ personality types were considered as an intervening variable. Data were collected through questionnaires, pre-tests, and post-tests and analyzed using SPSS 23. The results showed that the Think-Pair-Square model assisted by podcast media was more effective than the Think-Pair-Share model assisted by podcast media. The paired sample t-test results in both classes showed a significance value (2-tailed) of 0.000 (<0.05), indicating significant differences between pre-test and post-test scores. The independent sample t-test on post-test data showed a significance value (2-tailed) of 0.036 (<0.05), indicating a significant effect. The N-gain value in the experimental class was 0.41 (medium category), while the control class obtained 0.27 (low category). Descriptive statistics indicated that students with extraverted personality types achieved higher scores in both classes.